ââQUALITY SELF CARE AND HOME CAREââ SOLUSI KESEHATAN GIGI DAN MULUT ANAK TUNANETRA DI SDLB A-YKAB SURAKARTA - Agnintia, Dian; Rachmawati, Fauziah; Arsita, Riezky; Berti, Pamela Lolita (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Levels of health and poor oral hygiene is a problem that often occurs to blind children. Lack of knowledge and awareness of blind children and the parentâs role in maintaining oral health is one of the reasons. Quality self care and home care with dental care approach applicable to blind children to change their behavior in maintaining oral health. Measurement of the success rate of this program is to compare the results of the examination OHI-S (Oral Hygiene Index-Simplified) beginning, follow-up, and ending. There is a higher improvement of students with OHIS in good categories 13% at the beginning examination, 50% at follow-up examination, and 75% at the end of the examination.